Pengaruh Prenatal Yoga terhadap Kadar Hemoglobin dan Pengurangan Keluhan Fisik pada Ibu Hamil Trimester III - Asti Andriyani; Lusinta Agustin (Jurnal MID-Z (MIDWIFERI ZIGOT), 2022)
Changes in the body and psyche are felt by pregnant women and are often considered uncomfortable. One of the efforts to overcome discomfort by doing physical activity is prenatal yoga. 'The benefits of doing 'prenatal yoga' are reduced 'physical complaints and hemoglobin levels' can be increased. The aim is to know the effect of prenatal yoga on hemoglobin levels and the reduction of physical complaints in third trimester pregnant women. Quasi experimental research design (pre experiment) with a pre test and post test design approach. The area of ​​Daleman Tulung Klaten is the research location used. The population is all pregnant women, totaling 61 people and a sample of 20 respondents from the control group and 20 respondents from the treatment group. By purposive sampling. The results showed the effect of prenatal yoga on hemoglobin levels and reduction of physical complaints in third trimester pregnant women